2021
DOI: 10.1038/s41598-021-83547-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative conversion of biomass in giant DNA virus infection

Abstract: Bioconversion of organic materials is the foundation of many applications in chemical engineering, microbiology and biochemistry. Herein, we introduce a new methodology to quantitatively determine conversion of biomass in viral infections while simultaneously imaging morphological changes of the host cell. As proof of concept, the viral replication of an unidentified giant DNA virus and the cellular response of an amoebal host are studied using soft X-ray microscopy, titration dilution measurements and thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…The first description of vacuolar (H+)-ATPase highlights the close proximity of V and F-type of ATPase D in their catalytic function (Nelson et al, 1995). Recently, during a giant viral infection, it was shown that the shift of the carbonaceous biomass of the host concerned 6-17% for viral production, probably due to a Cedratvirus (Kördel et al, 2021). This observation underlined the fact that viral production requires a greater production of energy by the infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…The first description of vacuolar (H+)-ATPase highlights the close proximity of V and F-type of ATPase D in their catalytic function (Nelson et al, 1995). Recently, during a giant viral infection, it was shown that the shift of the carbonaceous biomass of the host concerned 6-17% for viral production, probably due to a Cedratvirus (Kördel et al, 2021). This observation underlined the fact that viral production requires a greater production of energy by the infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Kördel et al [ 50 ] studied the transfer of a substance from the host cell to the virus during the development of an unidentified giant DNA virus (presumably Cedratvirus) infecting the amoeba Acanthamoeba castellanii . Updated data were obtained on the number of virions formed during viral replication.…”
Section: Applications Of Sx Microscopy In Cell Biologymentioning
confidence: 99%
“…A structure has been discovered which may potentially be a viral replication factory. It has been shown that the changes affect the contractile vacuole and phagosomes, but not the nucleus, which allows the cell to function until lysis, increasing the efficiency of virus production [ 50 ]. The linear dependence of absorption coefficients on the organic matter concentration, visualized in cryo-SXT images, combined with the ability to process the entire cell volume, makes cryo-SXT a preferred tool for conducting this type of research, compared to EM, which allows the detection of much smaller virions but imposes restrictions on sample volumes.…”
Section: Applications Of Sx Microscopy In Cell Biologymentioning
confidence: 99%
See 2 more Smart Citations